2022
DOI: 10.3390/ncrna8030040
|View full text |Cite
|
Sign up to set email alerts
|

LINC00892 Is an lncRNA Induced by T Cell Activation and Expressed by Follicular Lymphoma-Resident T Helper Cells

Abstract: Successful immunotherapy in both solid tumors and in hematological malignancies relies on the ability of T lymphocytes to infiltrate the cancer tissue and mount an immune response against the tumor. Biomarkers able to discern the amount and the types of T lymphocytes infiltrating a given tumor therefore have high diagnostic and prognostic value. Given that lncRNAs are known to have a highly cell-type-specific expression pattern, we searched for lncRNAs specifically expressed by activated T cells and at the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The results showed that compared to IOSE80 cells, exosomes from SKOV3 and OVCAR8 cells had higher expression of AC134312.1, AC010834.3, LEMD1.AS1, PCOLCE.AS1, LINC00892, and AL138820.1. Research has shown that high expression of lncRNA is associated with the proliferation of ovarian cancer cells, activation of the PI3K-AKT pathway, T cell activation, and immune infiltration in the tumor microenvironment (63)(64)(65)(66). However, this trend was not observed in OC tissues from the TCGA datasets except LINC00892.…”
Section: Discussionmentioning
confidence: 96%
“…The results showed that compared to IOSE80 cells, exosomes from SKOV3 and OVCAR8 cells had higher expression of AC134312.1, AC010834.3, LEMD1.AS1, PCOLCE.AS1, LINC00892, and AL138820.1. Research has shown that high expression of lncRNA is associated with the proliferation of ovarian cancer cells, activation of the PI3K-AKT pathway, T cell activation, and immune infiltration in the tumor microenvironment (63)(64)(65)(66). However, this trend was not observed in OC tissues from the TCGA datasets except LINC00892.…”
Section: Discussionmentioning
confidence: 96%
“…In particular, CD4 + effector memory subtypes exhibit the highest expression of LINC00892. This enables LINC00892 to be a potential biomarker for activated T cells [60]. LINC01352 is notably downregulated in hepatitis B virus (HBV)/HBV X protein (HBx)-positive liver cancer cells and tissues.…”
Section: Discussionmentioning
confidence: 99%
“… 2018 ; Iaccarino et al. 2022 ). These ncRNAs can regulate gene expression through epigenetic modification, transcription and post-transcription, and participate in various biological processes such as cell differentiation, proliferation and apoptosis (Zhong et al.…”
Section: Introductionmentioning
confidence: 99%